Avaliação da atividade antidepressiva e ansiolítica do óleo essencial da C. Articulatus L. - LOPES, Jander Marcus Cirino (Universidade Federal do Oeste do Pará, 2023)
The mental disorders that most affect humanity are depression and anxiety, where depression is described as depressed and persistent mood, since anxiety refers to emotional and physiological manifestations such as tensions or exaggerated fears. Pharmacological treatments available on the market today have a variety of adverse effects, therefore, the project seeks new therapeutic alternatives that are effective in the treatment of depression and anxiety with less adverse effects. The objective of this study was to evaluate the antidepressant and anxiolytic activity of the essential oil of Cyperus articulatus L., in vivo in experimental models. For this purpose, the research was approved by the Ethics Committee on Animal Use (CEUA/UFOPA). The plant material of cyperus articulatus came from the Experimental Farm of the Federal University of Western Pará (UFOPA) and the chemical characterization was carried out by hydrodistillation in a clevenger-type apparatus. In the experimental tests, male and female mice of the Swiss strain, multiparous, non-pregnant and healthy were used. The chemical characterization of the essential oil of cyperus articulatus showed as major compounds: α-copaene (2.87%), β-selinene (4%), caryophyllene oxide (2.99%), mustacone (21.43%), cyperotundone (3.86%), cis-tujopsenal (7.70%), cyclocolorenone (11.94%). In the evaluation of acute oral toxicity, it was observed that the acute toxic dose is greater than 2000 mg/kg, classifying it in category 5 according to the criteria of the protocol adopted by OECD-423/2001. Thus, the results of tests carried out to evaluate antidepressant activity showed that the essential oil of Cyperus articulatus L., significantly reduced the parameter of immobility time in the forced swimming test at the concentration 400mg/kg by 64.60% (44.6 ± 3,36), when compared to the control group, indicating an antidepressant-like effect. In the test to evaluate anxiolytic activity performed with essential oil of Cyperus articulatus L, in this study, it was shown that the animals significantly increased the time spent in the open arms of the elevated plus maze at a concentration of 400 mg/Kg (151.8 ± 8 ,90), indicating an anxiolytic effect. In view of this, it can be inferred that the essential oil of Cyperus articulatus L., can contribute to the search for new approaches and therapeutic alternatives for the treatment of depression and anxiety, but further studies are needed for a more in-depth investigation of its antidepressant effect. and anxiolytic.